Propuesta diseño de tratamiento de aguas residuales generadas en la unidad de diálisis del hospital Quito n°1 – Policía Nacional del Ecuador. - Pilco Cedeño, Andrea Mishell (2021)
Hospital wastewater contains pathogenic microorganisms and substances of variable toxicity such as drugs, personal hygiene products and disinfectants, so its discharge without proper treatment constitutes an important environmental problem. The dialysis unit of Hospital Quito N ° 1 provides its service to people who suffer from chronic renal failure in Ecuador, whose treatment must be carried out three times a week, with the help of a dialyzer filter, which performs the purifying and normalizing function of the fluid and blood composition. Disinfection of these equipment as well as instruments carries toxins from the patients. This waste liquid is dumped directly into the sewer system, causing progressive contamination of the water. The investigation proposed a treatment of wastewater generated in the dialysis unit of Hospital Quito N ° 1 - National Police of Ecuador, for which an analysis of laboratory data provided by the same institution was carried out. Through the qualitative multimethodic approach, where it was possible to evaluate the results of physical, chemical and microbiological parameters of the years 2017, 2018 and 2019 from the wastewater of this unit. Where the parameters BOD (421 mg / l - 01/30/2017), COD (1002 mg / l - 01/30/2017) and SAAM (6,852 mg / l-06/10/2019) are not within the Maximum permissible discharge limits to the sewerage system of the Metropolitan District of Quito. Through the relationship between BOD5 and COD whose value is less than 2, it was directed towards a biological treatment line for the management proposal where this project gave a proposal for a wastewater treatment of the unit, giving as a treatment line to a grease trap system, a biodigester and the disinfection of the effluent before its drainage to the sanitary sewer. The main objective of these treatments is to reduce or completely eliminate the pollutant load of the liquid discharge, transforming it into a final effluent that complies with the corresponding environmental regulations and it would be harmless to the environment or il would have a less impact of contamination.